Penalty Prescriptive Decision as a Tool to Prevent Adverse Influence on the Environment - Korzeniowski, Piotr (Acta Universitatis Lodziensis. Folia Iuridica, 2020)
The aim of this paper is to discuss the main issues related to penalty prescriptive decisions, used by environmental protection authorities pursuant to the Act of 27th April 2001 on the environmental protection. The question of the legal instruments to prevent adverse influence on the environment has been discussed since many years. There are many publications in the literature devoted to this problem. As it can be seen from the number of the judgements issued by the Supreme Administrative Court, the practical side of the problem is of significance. For this reason, it is worth to make once again an attempt to analyse Art. 363 of the Act of 27th April 2001 on the environmental protection, which would constitute an attempt to make a certain synthesis of the problems arising from the application of such decisions.